Fibrillar Networks of Glycyrrhizic Acid for Hybrid Nanomaterials with Catalytic Features1. (10th March 2015) - Saha, Abhijit; Adamcik, Jozef; Bolisetty, Sreenath; Handschin, Stephan; Mezzenga, Raffaele
Abstract Self‐assembly of the naturally occurring sweetening agent, glycyrrhizic acid (GA) in water is studied by small‐angle X‐ray scattering and microscopic techniques. Statistical analysis on atomic force microscopy images reveals the formation of ultralong GA fibrils with uniform thickness of 2.5 nm and right‐handed twist with a pitch of 9 nm, independently of GA concentration. Transparent nematic GA hydrogels are exploited to create functional hybrid materials. Two‐fold and three‐fold hybrids are developed by introducing graphene oxide (GO) and in situ‐synthesized gold nanoparticles (Au NPs) in the hydrogel matrix for catalysis applications. In the presence of GO, the catalytic efficiency of Au NPs in the reduction of p‐nitrophenol to p‐aminophenol is enhanced by 2.5 times. Gold microplate single crystals are further synthesized in the GA hydrogel, expanding the scope of these hybrids and demonstrating their versatility in materials design.